Cultivares de Caqui Japonés en Florida - Ali Sarkhosh; Peter C. Andersen; Dustin Huff; Jonathan Clavijo Herrera (EDIS)
This is the Spanish version of: Sarkhosh, Ali, Peter Andersen, and Dustin Huff. 2020. “Japanese Persimmon Cultivars in Florida”. EDIS 2020 (1). https://doi.org/10.32473/edis-mg242-2020.